Study of interactions between conflicting parties of social and labor relations - Volodchenkova, Daryna; Volodchenkova, Natalia (My University, 2018)
The process of management in any organization is often accompanied by conflicts between individuals, or between teams. In most cases such situations lead to stress among employees, tense relationship within teams, and consequently, to decrease in efficiency of the company. That is why, conflicts and approaches to manage them, are crucial in our days. Ten employees of Diamond company took part in this psychological testing. The main task of this test is to identify the level of friendship, to determine the level of self-control of employees and also to determine the style of their behavior in conflict situations.Analysis of Diamond company helped to discover that there are various reasons for the conflict emergence in the enterprise. Therefore, the implementation of several training programs to solve problematic conflict situations can be suggested to the management of the company in order to raise ratings and to improve the psychological climate in teams.
Keywords: кафедра екології та екоменеджменту; conflict; management; stress; self-control; employee; labor relations; конфлікт; управління; стрес; самоконтроль; працівник; трудові відносини